PENERAPAN METODE FUZZY TSUKAMOTO DALAM PENENTUAN JUMLAH PRODUKSI ROTI (STUDI KASUS: DWI JAYA BAKERY KUPANG) - Yunni Alvionita Adoe; Kornelis Letelay; Emerensye Sofia Yublina Pandie (Program Studi Matematika, Universitas Nusa Cendana, 2022)
Dwi Jaya Bakery is a private business engaged in the production of food and bread. There are 4 types of bread in production that is: Small Chocolate Bread, Mocca Small Bread, Large Chocolate Fried Bread and Large Abon Bread. In this study the author applies the fuzzy tsukamoto method to determine the amount of bread production with 3 calculation stages is defining variables, inference and affirmation (defuzzification). The input variables used are demand and stock as well as the output variable is the amount of production. Production data obtained from Dwi Jaya Bakery industry is data from September 2018 - February 2019. For testing, the data used are 28 data for each type of bread is on the 1st to the 28th of february 2019, which has been added to the transformation equation and tested using the MAPE (Mean Absolut Percentage Error) where the error value will be searched for data on each type of bread. The error value obtained by applying the testing MAPE test method that has been added to the transformation equation for the type of small chocolate bread is 1,936786%, mocca small bread is 6,209643%, large chocolate fried bread is 3,886071% and large abon bread is 6,646429%.